Analysis of the Performance Achievement of Substitute Employees During Leave at Simpang Lima Gumul Regional Public Hospital Kediri - Sulistiono, Blesscindy Estherina; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to describe in detail the employee leave application procedures implemented at RSUD Simpang Lima Gumul Kediri and to analyze the performance achievements of substitute employees, particularly in terms of their competencies and the quality of services delivered during the main employees' leave period. Design/Methode/Approach : The research adopts a qualitative case study approach. Data were collected through interviews, direct observations, and documentation reviews. Informants were selected using purposive sampling based on the 5R criteria (Relevance, Recommendation, Rapport, Readiness, Reassurance). Research Finding : The leave process at RSUD SLG is manual and lacks standard handover procedures. Substitutes are appointed informally without training, yet generally perform well despite increased workloads. Operational efficiency is limited by the absence of digital systems and clear guidelines. Theoretical contribution/Originality : This research contributes to the body of knowledge in Human Resource Management by highlighting the gap in substitute performance management within public health institutions. It also emphasizes the need for procedural standardization and digital transformation in leave management systems—especially for non-civil servant employees (Non-ASN). Practitionel/Policy implication : The findings suggest that RSUD SLG should implement a digital leave management system, establish formal standard operating procedures (SOPs) for task delegation, and conduct regular training for substitute employees. These improvements can enhance service continuity and reduce administrative bottlenecks. Research limitation : This study is limited to administrative staff and Non-ASN employees within a single public hospital (RSUD SLG Kediri). The findings may not be generalizable to other hospital settings or employee categories such as PNS (Civil Servants).